Influence of pH on heavy metal speciation and removal from wastewater using micellar-enhanced ultrafiltration - Huang, Jinhui; Yuan, Fang; Zeng, Guangming; Li, Xue; Gu, Yanling; Shi, Lixiu; Liu, Wenchu; Shi, Yahui (Chemosphere (Oxford), 2017)
pH plays an important role in heavy metal removal during micellar-enhanced ultrafiltration (MEUF). In the present work, the influence of pH on heavy metal speciation and removal from wastewater by MEUF was investigated using an anionic surfactant (sodium dodecyl sulfate, SDS) and a hydrophilic membrane (polyether sulfone). Experiments were performed with pH values in the range of 1–12. Metal ion removal efficiency (R) was used to assess the effects of the MEUF process. Results showed that better removal rate of copper and cadmium was achieved at high pH values (pH > 3) with SDS feed concentration of 8 mM, while the optimal pH range was 3–10 for zinc and lead. The corresponding efficiencies for heavy metal removal decreased with the increasing feed concentration of metal ions under the pH conditions of 1–12. Furthermore, the heavy metal ion removal rate (50 mg/L) followed the order of Pb2+ > Cd2+ > Zn2+ > Cu2+. These results showed that pH is a key parameter in metal ion speciation and removal during MEUF. •Heavy metal speciation under different pH was simulated using Visual MINTEQ.•The effect of pH on heavy metal removal during MEUF was investigated.•A correlation for heavy metal ions speciation and removal efficiency was developed.